Caio, O Matemago: uma abordagem para uso dos videogames como ferramenta de suporte no ensino-aprendizagem de matemática - Melo, Lucas de Aquino (2018)
Video games were invented in the mid-twentieth century as an entertainment-oriented media that used the technological advances in computer Science to create interactive visual experiences based on game mechanics. In less than 50 years, video games ascended from being simple children's toys to becoming cultural symbols that are present in the most diverse cultures around the world and the main products in the multibillion dollar entertainment industry. The application plan proposed in this document presents the prototype of the educational game Caio, The Matemagician. This game intents to use the power of engagement and awe generated by videogames to foster the interest of young students to learn arithmetics and to provide a supporting tool for teachers in their pedagogical practices. When the video game is presente in an educational environment it creates around itself a media ecosystem that qualifies it to be used as an educational tool. By means of a transmedia branding strategy, it is possible to demonstrate the applications of videogames in this context in addition to establishing the emotional ties evoked by the digital game so that it can be used effectively in Education.